1999
DOI: 10.1083/jcb.146.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore Fibers Are Not Involved in the Formation of the First Meiotic Spindle in Mouse Oocytes, but Control the Exit from the First Meiotic M Phase

Abstract: During meiosis, two successive divisions occur without any intermediate S phase to produce haploid gametes. The first meiotic division is unique in that homologous chromosomes are segregated while the cohesion between sister chromatids is maintained, resulting in a reductional division. Moreover, the duration of the first meiotic M phase is usually prolonged when compared with mitotic M phases lasting 8 h in mouse oocytes.We investigated the spindle assembly pathway and its role in the progression of the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(64 citation statements)
references
References 26 publications
8
56
0
Order By: Relevance
“…The exact timing of stable correct KT-MT attachment in oocytes, however, remains uncertain. In the 1990s, an electron microscopic study detected stable endon KT-MT attachments at only the very late stage of phase 4 (Brunet et al, 1999). Recent immunostaining studies, however, have revealed end-on KT-MT attachments near phase 3 (Gui and Homer, 2012;Kitajima et al, 2011;Lane et al, 2012), although it is unknown whether these attachments are associated with bivalent stretching.…”
Section: Introductionmentioning
confidence: 92%
“…The exact timing of stable correct KT-MT attachment in oocytes, however, remains uncertain. In the 1990s, an electron microscopic study detected stable endon KT-MT attachments at only the very late stage of phase 4 (Brunet et al, 1999). Recent immunostaining studies, however, have revealed end-on KT-MT attachments near phase 3 (Gui and Homer, 2012;Kitajima et al, 2011;Lane et al, 2012), although it is unknown whether these attachments are associated with bivalent stretching.…”
Section: Introductionmentioning
confidence: 92%
“…One possibility that would attempt to unify the data is that there are certain types of kinetochore-microtubule attachments that are poorly detected and corrected in oocytes. In addition, end-on microtubule-kinetochore attachments are not formed until very late in meiosis I (Brunet et al 1999). Hence, there is an interest in this study and also in previous studies, in determining whether Auroras have any SAC role in the unusual first division of oocytes.…”
Section: The Role Of the Sac In Oocytesmentioning
confidence: 97%
“…This acceleration of meiosis I complements findings in mouse oocytes where, by various nocodazole incubations, the period of meiosis I most sensitive to delay by nocodazole treatment was found to be 6-8 h after NEB (Brunet et al 1999). In this study, we wanted to test whether ZM447439 would overcome a SAC arrest imposed by nocodazole.…”
Section: Zm447439 Overcomes a Nocodazole-imposed Sac Arrestmentioning
confidence: 97%
See 1 more Smart Citation
“…these results suggest that in vertebrate oocytes that lack centrosomes, one major function of Aur-B is to stabilize chromosome-associated spindle microtubules to ensure spindle bipolarity. 11,12 characterized by barrel shape, with chromosomes appearing "imbedded" within the dense microtubule network and with no prominent kinetochore microtubules. Studying spindle microtubule dynamics in the presence of excess MCAK or Op18/Stathmin, another microtubule-destabilizing protein, have revealed that only 5% of microtubules are kinetochore microtubules, 13,14 and the rest belong to two functionally distinct non-kinetochore microtubules, polar array microtubules (similar to aster microtubules in mitosis) and barrel array microtubules.…”
Section: Introductionmentioning
confidence: 99%